Single Step Formation of C-TiO2 Nanotubes: Influence of Applied Voltage and Their Photocatalytic Activity under Solar Illumination - Chin Wei Lai; Srimala Sreekantan (International Journal of Photoenergy)
Self-aligned and high-uniformity carbon (C)- titania (TiO2) nanotube arrays were successfully formed via single step anodization of titanium (Ti) foil at 30 V for 1 h in a bath composed of ethylene glycol (EG), ammonium fluoride (NH4F), and hydrogen peroxide (H2O2). It was well established that applied voltage played an important role in controlling field-assisted oxidation and field-assisted dissolution during electrochemical anodization process. Therefore, the influences of applied voltage on the formation of C-TiO2 nanotube arrays were discussed. It was found that a minimal applied voltage of 30 V was required to form the self-aligned and high-uniformity C-TiO2 nanotube arrays with diameter of ~75 nm and length of ~2 μm. The samples synthesized using different applied voltages were then subjected to heat treatment for the conversion of amorphous phase to crystalline phase. The photocatalytic activity evaluation of C-TiO2 samples was made under degradation of organic dye (methyl orange (MO) solution). The results revealed that controlled nanoarchitecture C-TiO2 photocatalyst led to a significant enhancement in photocatalytic activity due to the creation of more specific active surface areas for incident photons absorption from the solar illumination.